Does Transection of the Superficial MCL During HTO Result in Progressive Valgus Instability?. Issue 1 (January 2022) - Kim, Joo-Hwan; Ryu, Dong Jin; Lee, Sung-Sahn; Jang, Seung Pil; Park, Jae Sung; Kim, Won Jae; Kim, Il-Su; Wang, Joon Ho
Background: During high tibial osteotomy (HTO), the superficial medial collateral ligament (sMCL) is cut or released at any degree to expose the osteotomy site and achieve the targeted alignment correction according to the surgeon's preference. However, it is still unclear whether transection of sMCL increases valgus laxity. Purpose: We aimed to assess the outcomes and safety of sMCL transection, especially focusing on iatrogenic valgus instability. Study Design: Case series; Level of evidence, 4. Methods: Seventy-two patients (89 knees) who underwent medial open wedge HTO (MOWHTO) with transection of the sMCL between October 2013 and September 2018 were retrospectively investigated. Clinical evaluations, including the International Knee Documentation Committee (IKDC) score, Knee injury and Osteoarthritis Outcome Score (KOOS), and Tegner and Lysholm scores, were performed preoperatively and at 2 years postoperatively. The radiographic parameters hip-knee-ankle (HKA) angle, joint line convergence angle on standing radiographs (standing JLCA), and weightbearing line (WBL) ratio were assessed preoperatively and at 3 months, 6 months, 1 year, and 2 years postoperatively. To evaluate valgus laxity, we assessed the valgus JLCA and medial joint opening (MJO) at the aforementioned time points using valgus stress radiographs. Results: All clinical results at the 2-year follow-up were significantly improved compared with those obtained at the preoperative assessment ( P < .001). The postoperative HKA angle significantly differed from the preoperative one, and no significant valgus progression was observed during follow-up (preoperative, 8.5°± 2.7°; 3 months, –3.5°± 2.0°; 6 months, –3.2°± 2.3°; 1 year, –3.1°± 2.3°; 2 years, –2.9°± 2.5°; P < .001) The mean WBL ratio was 62.5% ± 9.0% at 2 years postoperatively. The postoperative valgus JLCA at all follow-up points did not significantly change compared with the preoperative valgus JLCA (preoperative, –0.1°± 2.1°; 3 months, –0.2°± 2.4°; 6 months, –0.1°± 2.5°; 1 year, 0.1°± 2.5°; 2 years, 0.2°± 2.2°) The postoperative MJO at all follow-up points did not significantly change compared with the preoperative MJO (preoperative, 7.1 ± 1.7 mm; 3 months, 7.0 ± 1.7 mm; 6 months, 6.9 ± 1.9 mm; 1 year, 6.7 ± 1.8 mm; 2 years, 6.8 ± 1.8 mm). Conclusion: Transection of the sMCL during MOWHTO does not increase valgus laxity and could yield desirable clinical and radiographic results.